STRUCTURAL CHARACTERISTICS OF DENSIFIED SILICON NITRIDE UNDER HIGH PRESSURE: A MOLECULAR DYNAMICS STUDY - Cong Thanh, Dinh; Thi Thao, Nguyen; Van Vinh, Le (HNUE Journal of Science: Journal of Natural Sciences, 2025)
We used molecular dynamics (MD) simulations to investigate the structural properties of silicon nitride (Si3N4) at high temperatures and pressures. The Si3N4 models were cooled under a pressure of 75 GPa. A phase transition occurred in the temperature range of 3950 K to 3650 K. The structural characteristics of these Si3N4 models were analysed. At 4500 K and 4000 K, the Si3N4 models exhibited a disordered structure. As the temperature decreased, the nitrogen (N) atoms predominantly adopted a face-centered cubic (fcc) structure, and a significant fraction of N atoms exhibited hexagonal close-packed (hcp) and other disordered motifs. The hcp and disordered regions were interspersed among fcc sublattices with different orientations. The local entropy distribution of the atoms broadened and shifted toward lower values with decreasing temperature.